Christmas in the city - Richards, Kitty; Durk, Jim (New York, N.Y. : Simon Spotlight/Nickelodeon, 2003)
The Rugrats look for Santa all over New York City but just keep missing him. Where can he be?
"Nickelodeon."
84124
Keywords: Rugrats (Television program) -- Juvenile fiction; Christmas -- Juvenile fiction; Santa Claus -- Juvenile fiction; Infants -- Juvenile fiction